La formation qualifiante : une transition vers l’emploi pour les jeunes chercheurs d’emploi bruxellois peu scolarisés ? - Matthieu Veinstein; Isabelle Sirdey (Brussels Studies, 2016)
The French-speaking professional training system in Brussels significantly improves the opportunities for the professional integration of participants, in particular with respect to vocational training. The possible impact of this – particularly as a second chance for young people with the lowest qualifications – is, however, limited by the recruitment practices of companies. While they generally favour those who have undergone vocational training, other criteria are taken into consideration when there is a shortage of job vacancies. The most vulnerable youth benefit less from their vocational training, especially in terms of job stabilisation. It therefore seems necessary to combine economic development and the safeguarding of educational pathways in order to take action against unemployment in Brussels.